One year of solar extinction measurements at Plataforma Solar de Almería. Application to solar tower plants. (June 2019) - Ballestrín, J.; Carra, E.; Monterreal, R.; Enrique, R.; Polo, J.; Fernández-Reche, J.; Barbero, J.; Marzo, A.; Alonso-Montesinos, J.; López, G.; Batlles, F.J.
Abstract: The thermoelectric solar tower plants have had a great development in the last years, evolving from a few MWe to reach a hundred MWe. The location of these large plants in desert areas leads to very specific problems in their design and great uncertainty among CSP promoters. In particular, there is no reliable information on the losses due to solar extinction between the heliostats and the receiver. Consistent information on solar extinction at the chosen site would be desirable in the design phase of the plant and later during its regular operation. Currently, a novel and reliable solar extinction measurement system is daily working at Plataforma Solar de Almería (PSA). After a year of extinction measurements, it has been possible to analyze the daily and seasonal variability of the extinction phenomenon and know the annual extinction average value at PSA. Highlights: One year of measures of solar extinction at PSA is analyzed. Higher solar extinction values and greater variability in the warm months. The obtained average annual extinction coefficient at PSA is 0.081 km −1 .